Association between age, gender and education level with the severity of periodontitis in pre-elderly and elderly patients - Pitu Wulandari; Dody Widkaja; Aini Hariyani Nasution; Armia Syahputra; Gebby Gabrina (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: As individuals grow older, they may be more susceptible to chronic diseases, which can affect their overall health. Periodontitis, for instance, is one of the most common oral diseases that result from prolonged exposure to pathogens. The main etiology of periodontitis is dental biofilms, but several risk factors may also affect the progression of the disease. Purpose: The study aimed to determine whether there was an association between age, gender and education level and the severity of periodontitis using the 2017 American Academy of Periodontology (AAP) classification. Methods: A retrospective analytical study was used to determine the stage and grade of periodontitis in relation to age, gender and education level. Secondary data in the form of medical record status was analysed using software applications. Results: The distribution of periodontitis was 66.7% in pre-elderly patients (45–59 years), 61.5% in male subjects and 39.7% in individuals with middle education levels. Using chi-square analysis, the severity of periodontitis showed a statistically significant correlation with age (p=0.01) and gender (p=0.003). In contrast, the level of education was not statistically correlated to the severity of periodontitis (p=0.887). The percentage of stage IV grade B was highest in elderly patients (65.38%), while stage IV grade C was the highest in male subjects (41.67%). Conclusion: The study showed that age and gender significantly influenced the occurrence and severity of periodontitis, while education level showed the opposite.